the seventeenth term of an ap is 5 morethan twice its eighteenth term . If the 11 term of the ap is 43 find its nth term
Answers
Answered by
10
Answer:
nth term = 109 - 6n
or
103 - 6(n-1)
Step-by-step explanation:
nth term of an ap = a + (n-1)d
17th Term = a + (17-1)d = a + 16d
18th term = a + (18-1)d = a + 17d
17th term = 2 * (18th term) + 5
a + 16d = 2 * ( a+ 17d) +5
a +16d = 2a + 34d + 5
a + 18d = - 5 Eq 1
11th term = a + (11-1)d = a + 10d
a + 10d = 43 Eq 2
Eq 1 - Eq 2
8d = -48
d = -6
a + 10(-6) = 43
a = 103
nth rem = 103+ (n-1)(-6)
= 103 - 6(n-1)
= 103 - 6n + 6
= 109 - 6n
Answered by
23
a17 = a+16 d
a18 = a+17 d
![\textbf{\underline{Given that :-}} \textbf{\underline{Given that :-}}](https://tex.z-dn.net/?f=%5Ctextbf%7B%5Cunderline%7BGiven+that+%3A-%7D%7D)
a17 = 5 + 2 × a18
a+16d = 5+ 2(a+17 d)
a+16 d = 5+2a+34d
16d-34d -5 =2a-a
![\boxed{ \bf{ - 18 \: d - 5 = a}} \boxed{ \bf{ - 18 \: d - 5 = a}}](https://tex.z-dn.net/?f=+%5Cboxed%7B+%5Cbf%7B+-+18+%5C%3A+d+-+5+%3D+a%7D%7D)
a11 =43
a+10d = 43
-18d -5 +10d =43
-8d -5 =43
-8d =43+5
-8d =48
![\bf{d = \frac{48}{ - 8} } \bf{d = \frac{48}{ - 8} }](https://tex.z-dn.net/?f=+%5Cbf%7Bd+%3D+%5Cfrac%7B48%7D%7B+-+8%7D+%7D)
![\boxed{ \bf{d = - 6}} \boxed{ \bf{d = - 6}}](https://tex.z-dn.net/?f=+%5Cboxed%7B+%5Cbf%7Bd+%3D+-+6%7D%7D)
a=-18 d -5
a= -18×-6 -5
a= 108 -5
![\boxed{ \bf{a = 103}} \boxed{ \bf{a = 103}}](https://tex.z-dn.net/?f=+%5Cboxed%7B+%5Cbf%7Ba+%3D+103%7D%7D)
![\underline{ \bf{a {\tiny{n}} \: = \: a + (n - 1)d }} \underline{ \bf{a {\tiny{n}} \: = \: a + (n - 1)d }}](https://tex.z-dn.net/?f=+%5Cunderline%7B+%5Cbf%7Ba+%7B%5Ctiny%7Bn%7D%7D+%5C%3A+%3D+%5C%3A+a+%2B+%28n+-+1%29d+%7D%7D)
an = 103 + (n-1) × -6
an =103 -6n +6
a18 = a+17 d
a17 = 5 + 2 × a18
a+16d = 5+ 2(a+17 d)
a+16 d = 5+2a+34d
16d-34d -5 =2a-a
a11 =43
a+10d = 43
-18d -5 +10d =43
-8d -5 =43
-8d =43+5
-8d =48
a=-18 d -5
a= -18×-6 -5
a= 108 -5
an = 103 + (n-1) × -6
an =103 -6n +6
SillySam:
Hehehe.... thnx... xD ❤☺
Similar questions